2018
DOI: 10.1039/c8cy00381e
|View full text |Cite
|
Sign up to set email alerts
|

Development of hydroxy-containing imidazole organocatalysts for CO2 fixation into cyclic carbonates

Abstract: Metal-free catalysts for cyclic carbonates synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…This phenomenon suggests that the high activity of I C2 HCP‐5b comes from the internal superior activity of the IL precursor. In addition, it is reported that the formation of strong hydrogen bonds between the hydroxy group of ILs and the epoxide would cause the shift or broadening of the 1 H NMR signal for the hydroxy group . However, no such phenomenon was observed when comparing the 1 H NMR spectra of 1‐benzyl‐3‐hydroxyethylimidazolium bromide and 1‐benzyl‐3‐hydroxyethylimidazolium bromide+epichlorohydrin mixture, suggesting that only weak hydrogen bonds form in this system, which may not be the determining parameter for the activity.…”
Section: Resultsmentioning
confidence: 92%
“…This phenomenon suggests that the high activity of I C2 HCP‐5b comes from the internal superior activity of the IL precursor. In addition, it is reported that the formation of strong hydrogen bonds between the hydroxy group of ILs and the epoxide would cause the shift or broadening of the 1 H NMR signal for the hydroxy group . However, no such phenomenon was observed when comparing the 1 H NMR spectra of 1‐benzyl‐3‐hydroxyethylimidazolium bromide and 1‐benzyl‐3‐hydroxyethylimidazolium bromide+epichlorohydrin mixture, suggesting that only weak hydrogen bonds form in this system, which may not be the determining parameter for the activity.…”
Section: Resultsmentioning
confidence: 92%
“…The reaction was also applied to diols; 1-phenylethan-1,2diol and 3-phenoxypropan-1,2-diol gave the corresponding cyclic carbonates in 95% and 58%, respectively. Then, the same research group proposed another catalytic mixture to perform the same reaction, that are: CuI (5 mol%) 1,10-phenantroline (5 mol%) t-BuOK (10 mol%), CO2 (0.5 MPa), 80 Then, the same research group proposed another catalytic mixture to perform the same reaction, that are: CuI (5 mol%) 1,10-phenantroline (5 mol%) t-BuOK (10 mol%), CO 2 (0.5 MPa), 80 • C, 12 h [178].…”
Section: Scheme 13mentioning
confidence: 99%
“…In the presence of atmospheric pressure CO 2 , 7 terminal epoxides were converted into cyclic carbonates in 80 %–95 % yields. Comparing with phenol‐functionalized imidazole‐based catalysts, lower temperature and pressure of CO 2 are permitted, which is caused by more hydroxyl groups of the catalysts. Internal epoxides are challenging substrates, and metal‐free catalysts active for internal epoxide reactions are rare .…”
Section: Resultsmentioning
confidence: 99%